2022
DOI: 10.1155/2022/6368219
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Study of Clopidogrel Combined with Huoxue Tongluo Prescription in Improving Transient Ischemic Attack and the Effect on MMP-9, Hcy, and CRP

Abstract: Background. This study aimed to explore the clinical study of clopidogrel combined with Huoxue Tongluo prescription in improving transient ischemic attack (TIA) and the effect on MMP-9, Hcy, and CRP. Methods. A total of 84 patients with TIA admitted to our hospital from December 2019 to February 2021 were selected. The patients were divided into the control group (42 cases: not treated with Huoxue Tongluo prescription) and study group (42 cases: treatment with Huoxue Tongluo prescription). The clinical efficac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…Studies have demonstrated that high HCY level can induce vascular injuries leading to intimal thickening, rupture of the elastic layer, smooth muscle hypertrophy, significant platelet dysfunction, and formation of platelet-rich occlusive thrombi ( 35 , 36 ). Elevated HCY could promote oxygen free radical generation and damage the vascular endothelium leading to platelet aggregation and thrombosis ( 37 ). Furthermore, a meta-analysis indicated that a non-linear association could exist between HCY levels and risk of IS ( 38 ).…”
Section: Discussionmentioning
confidence: 99%
“…Studies have demonstrated that high HCY level can induce vascular injuries leading to intimal thickening, rupture of the elastic layer, smooth muscle hypertrophy, significant platelet dysfunction, and formation of platelet-rich occlusive thrombi ( 35 , 36 ). Elevated HCY could promote oxygen free radical generation and damage the vascular endothelium leading to platelet aggregation and thrombosis ( 37 ). Furthermore, a meta-analysis indicated that a non-linear association could exist between HCY levels and risk of IS ( 38 ).…”
Section: Discussionmentioning
confidence: 99%